Alcohol Mixed with Energy Drink Use as an Event‐Level Predictor of Physical and Verbal Aggression in Bar Conflicts. (January 2016) - Miller, Kathleen E.; Quigley, Brian M.; Eliseo‐Arras, Rebecca K.; Ball, Natalie J.
Abstract : Background: Young adult use of alcohol mixed with caffeinated energy drinks (AmEDs) has been globally linked with increased odds of interpersonal aggression, compared with the use of alcohol alone. However, no prior research has linked these behaviors at the event level in bar drinking situations. The present study assessed whether AmED use is associated with the perpetration of verbal and physical aggression in bar conflicts at the event level. Methods: In Fall 2014, a community sample of 175 young adult AmED users (55% female) completed a web survey describing a recent conflict experienced while drinking in a bar. Use of both AmED and non‐AmED alcoholic drinks in the incident were assessed, allowing calculation of our main predictor variable, the proportion of AmEDs consumed (AmED/total drinks consumed). To measure perpetration of aggression, participants reported on the occurrence of 6 verbal and 6 physical acts during the bar conflict incident. Results: Linear regression analyses showed that the proportion of AmEDs consumed predicted scores for perpetration of both verbal aggression ( β = 0.16, p < 0.05) and physical aggression ( β = 0.19, p < 0.01) after controlling for gender, age, sensation‐seeking and aggressive personality traits, aggressive alcohol expectancies, aggressogenic physical and social bar environments, and total number of drinks. Conclusions: Results of this study suggest that in alcohol‐related bar conflicts, higher levels of young adult AmED use are associated with higher levels of aggression perpetration than alcohol use alone and that the elevated risk is not attributable to individual differences between AmED users and nonusers or to contextual differences in bar drinking settings. While future research is needed to identify motivations, dosages, and sequencing issues associated with AmED use, these beverages should be considered a potential risk factor in the escalation of aggressive bar conflicts.